5d+12=8d-3

Simple and best practice solution for 5d+12=8d-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5d+12=8d-3 equation:


Simplifying
5d + 12 = 8d + -3

Reorder the terms:
12 + 5d = 8d + -3

Reorder the terms:
12 + 5d = -3 + 8d

Solving
12 + 5d = -3 + 8d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-8d' to each side of the equation.
12 + 5d + -8d = -3 + 8d + -8d

Combine like terms: 5d + -8d = -3d
12 + -3d = -3 + 8d + -8d

Combine like terms: 8d + -8d = 0
12 + -3d = -3 + 0
12 + -3d = -3

Add '-12' to each side of the equation.
12 + -12 + -3d = -3 + -12

Combine like terms: 12 + -12 = 0
0 + -3d = -3 + -12
-3d = -3 + -12

Combine like terms: -3 + -12 = -15
-3d = -15

Divide each side by '-3'.
d = 5

Simplifying
d = 5

See similar equations:

| 3n+8=41 | | 7t+2=44 | | 10+5m=70 | | 4t+7=27 | | -4b+3=-33 | | 9+5w=69 | | 10n-9=9+4n | | 4w+10=-34 | | -2-4w=26 | | -10-4a=-10 | | 7n-7=28 | | 5k+3=33 | | 6+6x=-66 | | -5m+1=11 | | 4n+8=44 | | 10+7b=59 | | -5w+1=-29 | | 2x+15=6x+7 | | 2x^2=x^2/3+15 | | 7x-12=2+7x | | 3a-8=-8 | | 7+3w=22 | | -4a-7=-43 | | 8-6w=26 | | -1+4d=11 | | 7n+1=-13 | | -3x-2=31 | | 5n(2)+35=0 | | k-0.7=2.3 | | 6t-2=34 | | 7+6x=-41 | | 9-7a=30 |

Equations solver categories